Purinergic receptors play a key role in shock wave-induced proliferation - Dorota Szwarc-Hofbauer; Elisabeth Simböck; Carina Hromada; Michaela Stoiber; Janine Tomasch; Georg Weitzer; Andreas Teuschl-Woller (Scientific Reports)
Abstract Shock wave treatment (SWT) is a non-invasive therapy applied in musculoskeletal and urological disorders, as well as in chronic wound regeneration. As the use of medical SWT broadens, it is important to better understand the molecular mechanisms underlying its success. Here, we identified P2X4 and P2Y2 purinergic receptors to be primarily expressed in C3H/10T1/2 mouse mesenchymal stromal cells and investigated their role in the initiation of the signaling events following SWT using single- and double-receptor knock-out (KO) cell lines. We show that SWT induced the expression of c-Jun and c-Fos within 30 min after stimulation and that the SWT-induced Erk1/2 pathway activation and immediate early gene expression were decreased in P2Y2-, P2X4- and P2Y2/P2X4-deficient cells. Importantly, SWT did not promote proliferation in P2Y2/P2X4-deficient cells, while loss of either one of the receptors significantly reduced the proliferative effect, indicating a cumulative effect of their loss. Finally, our data suggests a more prominent role of the P2Y2 receptor in SWT-induced cellular effects, since primarily its loss contributed to the observed changes. With these findings, we further the understanding of the molecular mechanisms of SWT and propose that the varying expression of purinergic receptors in tissues should be considered when establishing treatment protocols.